Atma Insights: A Flexible Learning Tool to Enable Global Learners to Access Essential Business and Cross-Cultural Knowledge - Dunung, Sanjyot P (International Journal of Advanced Corporate Learning (iJAC), 2020)
This case provides a deeper understanding of how cross-cultural learning tools can be effectively utilized to enable professionals and companies optimize professional and personal development, improve communication, foster awareness, build trust, and align with global corporate objectives and benchmarks.